Upaya Meningkatkan Gerakan Meroda Menggunakan Pola Gerak Dominan dalam Pembelajaran Senam Lantai - Oksyalia, Dean; Suntoda, Andi; Mahendra, Agus; Hidayat, Agus (TEGAR: Journal of Teaching Physical Education in Elementary School, 2018)
Â The purpose of this research is to find out result of the implementations of a dominant movement pattern approach, in an effort to improve the skills of cartwheel on gymnastics learning. The research employed a Classroom Action Research Method to the participants of 39 student of grade five of SD Attazhimiyah Bandung, consisting 14 male students and 15 female students. The instrument to be used in this research is observational sheet, field notes and skill test. Based on the data processing, the preliminary observation data obtained an average score of 50.29, on cycle 1 action 1 the average score is 54.60, on cycle 1 action 2 the average score is 61.35, on cycle 2 action 2 the average score is 66.67, and on cycle 2 action 2 the average score is 75.57. The conclusion of this research is that the dominant movement pattern approach can effectively improve the skill of cartwheel movement of the students .Â AbstrakPenelitian ini bertujuan untuk mengetahui hasil implementasi pendekatan pola gerak dominan dalam upaya meningkatkan keterampilan gerakan meroda pada pembelajaran senam lantai. Metode penelitian yang digunakan adalah metode Penelitian Tindakan Kelas (PTK). Subjek dan objek dalam penelitian ini meliputi siswa kelas V SD Attazhimiyah Bandung yang berjumlah 29 orang, yang terdiri dari 14 siswa putera dan 15 siswa puteri. Instrumen yang digunakan dalam penelitian adalah observasi, catatan lapangan dan tes keterampilan. Berdasarkan hasil pengolahan data dan analisis diperoleh data observasi awal nilai rata-rata 50,29, siklus 1 tindakan 1 nilai rata-rata 54,60, siklus 1 tindakan 2 nilai rata-rata 61,35, siklus 2 tindakan 1 nilai rata-rata 66,67, siklus 2 tindakan 2 nilai rata-rata 75,57. Kesimpulan, implementasi pendekatan pola gerak dominan (PGD) dapat meningkatkan gerakan meroda dalam pembelajaran senam lantai pada siswa kelas V di SD Attazhimiyah Bandung.Â